PENERAPAN MODEL PEMBELAJARAN GQGA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SMP - Edelbertus Rahmat; Maria Fatima Mei; Konstantinus Denny Pareira Meke (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
The objectives of this study are 1) to determine student activities while applying the GQGA learning model to comparative materials; and 2) to find out the improvement of students' mathematics learning outcomes on comparative materials. The type of research used was Classroom Action Research (CAR). CAR is carried out in two cycles where each cycle is made in three meetings. Data collection techniques are learning outcomes tests and observations of learning implementation. The data analysis technique used qualitative data analysis techniques and quantitative data. The results showed that the application of the GQGA learning model could improve students' mathematics learning outcomes and student activities. This can be seen from the results of the analysis of student activity observations in the first cycle, which is 51.5%, and in the second cycle it reaches 91.5% and the results of the students' mathematics learning test in the first cycle is 58% and in the second cycle it reaches 92%, exceeding the KKM. Therefore, the researcher concludes that the application of the GQGA learning model can improve students' mathematics learning outcomes in comparative material.